Peter and Butch - Phipson, Joan, 1912-2003. (Croydon, Vic. : Longmans of Australia, 1969)
To prove his toughness, angelic looking Peter (Butch to his friends) gets involved with a group of young criminals. He is soon disillusioned with them and in so doing, Peter begins to grow up.
Muir, M. A bibliography of Australian children's books
For adolescents.
Keywords: Teenage boys -- Australia -- Juvenile fiction; Juvenile delinquents -- Australia -- Juvenile fiction